2019
DOI: 10.1051/0004-6361/201935598
|View full text |Cite
|
Sign up to set email alerts
|

A possibly inflated planet around the bright young star DS Tucanae A

Abstract: Context. The origin of the observed diversity of planetary system architectures is one of the main topics of exoplanetary research. The detection of a statistically significant sample of planets around young stars allows us to study the early stages of planet formation and evolution, but only a handful of them is known so far. In this regard, a considerable contribution is expected from the NASA TESS satellite, which is now performing a survey of ∼ 85% of the sky to search for short-period transiting planets A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 80 publications
2
69
1
Order By: Relevance
“…Newton et al (2019) find a planet radius of 5.70 ± 0.17 R ⊕ and a transit duration of 0.1324±0.0005 days, with the planet orbiting a G6V star with an effective temperature of 5430±80 K, and a model-dependent radius of 0.964 ± 0.029. Benatti et al (2019) similarly find a planet radius of 5.63 ± 0.22 R ⊕ and a transit duration of 0.119 days, with the planet orbiting a G6V star with an effective temperature of 5542 ± 21 K, and a model-dependent radius of 0.872 ± 0.027 R . We refer the reader to those two papers for a detailed discussion of the stellar parameters and transit fits.…”
Section: Introductionmentioning
confidence: 62%
“…Newton et al (2019) find a planet radius of 5.70 ± 0.17 R ⊕ and a transit duration of 0.1324±0.0005 days, with the planet orbiting a G6V star with an effective temperature of 5430±80 K, and a model-dependent radius of 0.964 ± 0.029. Benatti et al (2019) similarly find a planet radius of 5.63 ± 0.22 R ⊕ and a transit duration of 0.119 days, with the planet orbiting a G6V star with an effective temperature of 5542 ± 21 K, and a model-dependent radius of 0.872 ± 0.027 R . We refer the reader to those two papers for a detailed discussion of the stellar parameters and transit fits.…”
Section: Introductionmentioning
confidence: 62%
“…With this in mind, the Zodiacal Exoplanets in Time Survey (Mann et al 2016a), and its successor, the TESS Hunt for Young and Maturing Exoplanets (THYME; Newton et al 2019), set out to identify transiting planets in young clusters, moving groups, and star-forming regions with ages of 5-700 Myr using light curves from the K2 and TESS missions. Discoveries from these and similar surveys have found planets in diverse environments, from the 10-20 Myr Sco-Cen OB association (Rizzuto et al 2020), to the 45 Myr Tucana-Horologium moving group (Benatti et al 2019;Newton et al 2019), to as old as the 700 Myr Hyades cluster (Vanderburg et al 2018). More importantly, these discoveries have demonstrated that young planets are systematically larger than older planets of the same mass (Obermeier et al 2016;Mann et al 2018) and that at least some short-period planets migrate within the first 10 Myr or form in situ (David et al 2016b;Mann et al 2016b).…”
Section: Introductionmentioning
confidence: 77%
“…DS Tuc Ab (Benatti et al 2019;Newton et al 2019) is a 5.70 ± 0.17 R ⊕ planet 7 discovered around a 45 ± 4 Myr, 1.01 M star, orbiting with a period of 8.1 days. Using exactly the same formalism as applied in Section 3 we consider the constraints on entropy of formation and initial Kelvin-Helmholtz timescale as a function of planet mass.…”
Section: Ds Tuc Abmentioning
confidence: 99%